2022
DOI: 10.1158/0008-5472.can-21-2072
|View full text |Cite|
|
Sign up to set email alerts
|

Chromatin Rewiring by Mismatch Repair Protein MSH2 Alters Cell Adhesion Pathways and Sensitivity to BET Inhibition in Gastric Cancer

Abstract: Mutations in the DNA mismatch repair gene MSH2 are causative of microsatellite instability (MSI) in multiple cancers. Here, we discovered that besides its well-established role in DNA repair, MSH2 exerts a novel epigenomic function in gastric cancer (GC). Unbiased CRISPR-based mass spectrometry combined with genome-wide CRISPR functional screening revealed that in early-stage GC MSH2 genomic binding is not randomly distributed but rather is associated specifically with tumor-associated super-enhancers controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The group further reported that the phosphorylation at the C-terminal end of Brg1 regulated Brg1s subcellular localization [ 493 ]. The SWI/SNF chromatin remodeler Brg1 has been recently shown to be essential for the chromatin remodeling function of MSH2 [ 494 ]. Nargund et al demonstrated that MSH2 genomic binding in gastric cancer was associated specifically with tumor-associated super-enhancers controlling the expression of cell adhesion genes.…”
Section: Importance Of Ck2 In Different Hallmarks Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The group further reported that the phosphorylation at the C-terminal end of Brg1 regulated Brg1s subcellular localization [ 493 ]. The SWI/SNF chromatin remodeler Brg1 has been recently shown to be essential for the chromatin remodeling function of MSH2 [ 494 ]. Nargund et al demonstrated that MSH2 genomic binding in gastric cancer was associated specifically with tumor-associated super-enhancers controlling the expression of cell adhesion genes.…”
Section: Importance Of Ck2 In Different Hallmarks Of Cancermentioning
confidence: 99%
“…Nargund et al demonstrated that MSH2 genomic binding in gastric cancer was associated specifically with tumor-associated super-enhancers controlling the expression of cell adhesion genes. This binding has been required for chromatin rewiring, was independent of MSH2′s DNA repair catalytic activity and the SWI/SNF chromatin remodeler Brg1 was a prerequisite for recruitment to gene loci [ 494 ]. However, whether the CK2-mediated phosphorylation of Brg1 is directly involved in this process remains to be elucidated.…”
Section: Importance Of Ck2 In Different Hallmarks Of Cancermentioning
confidence: 99%
“…Correlation analysis revealed that most SRSF family expression is positively associated with MMR gene expression, particularly MLH1, MSH2, and MSH6. MSH2 has been shown to regulate the cancerassociated cell adhesion pathway and contribute to tumor aggressiveness (Nargund et al, 2022). Moreover, variants in MSH6 could lead to disease recurrence and poor survival after treatment for tumor (Zanusso et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of the mismatch repair protein MSH2 and the related MSH6 protein was associated with super-enhancer dysfunction in gastric cancer cells, independently of the role of the two proteins in mismatch repair [121]. Normal MSH2 in co-operation with MSH6 interacts with SWI/SNF protein SMARCA4 and loss of this interaction due to knockdown of MSH2 results in decreased acetylation of superenhancer sites with a particular enrichment in super-enhancers of cell adhesion associated genes, such as CLDN4, encoding for tight junction protein Claudin 4, ITGB1, encoding for integrin sub-unit beta 1, and CTNNB1, encoding for β-catenin.…”
Section: Target 6: Synthetic Lethalitymentioning
confidence: 98%